Process Oriented Guided Inquiry Learning in Nursing Education - Jeya Devi, Coomarasamy; Yusup, Hashim (2016)
Employers want graduates who have the confi dence and ability to make appropriate patient care decisions. This study was done to determine whether Process Oriented Guided Inquiry Learning (POGIL), would have an eff ect on the diploma in nursing students’ academic achievement and confi dence in learning. A convenience sample of students (n=73) were randomly assigned to two groups. A quasi-experimental study was conducted using pre-test/post-test together with a beginning /end of semester confi dence in learning surveys. To determine the perception of the students towards the new instructional method, a semi-structured interview was done amongst nine students from the experimental group. Signifi cant diff erence was found between the two groups towards confi dence in learning, but not in the post-test scores. Three main categories and nine themes emerged from the interviews which supported the quantitative fi ndings that POGIL as an instructional method has the potential to make a signifi cant contribution to nursing education. Keywords: POGIL, achievement level, confi dence in learning.